The Theory of Falling Shadows Applied to 𝑑-Ideals in 𝑑-Algebras - Young Bae Jun; Sun Shin Ahn (International Journal of Mathematics and Mathematical Sciences)
On the basis of the theory of a falling shadow which was first formulated by Wang (1985), the notion of falling 𝑑∗-ideals in 𝑑-algebras is introduced, and related properties are investigated. Characterizations of a falling 𝑑∗-ideal are established. Relations among falling 𝑑∗-ideals, falling 𝑑-ideals, falling 𝑑#-ideals, falling 𝑑-subalgebras, and falling BCK-ideals are discussed.